Emerging medical treatments for actinic keratoses, squamous cell carcinoma and basal cell carcinoma. (September 2012) - Ghuznavi, Nasreen; Nocera, Nadia F; Guajardo, Andrew R; Weinberg, Jeffrey M
Skin cancer is the most common cancer in the USA. Non-melanoma skin cancers, which include basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), comprise the majority. BCC and SCC are commonly treated with surgical excision, curettage, cryotherapy and radiation. Actinic keratoses (AK) are considered precursors of SCC and are commonly treated with 5-fluorouracil, imiquimod, diclofenac, liquid nitrogen or photodynamic therapy. On 5 March 2012 we conducted a Medline search for Phase II and III trials of novel medical treatments that have been reported within the last 3 years. We also searched clinicaltrials.gov to find promising treatments in development. Ingenol mebutate has been investigated as a treatment for AK, SCC and BCC. Dobesilate and the combination of 5-fluorouracil and salicylic acid were also studied for AK. Cetuximab, an EGF receptor inhibitor, was studied for SCC; and vismodegib, a Hedgehog inhibitor, was studied for BCC.